ADS-B data usage for aircraft noise and air quality modelling and measurement during specific stages of LTO cycle. (8th November 2022) - Kazhan, Kateryna; Synylo, Kateryna; Zaporozhets, Oleksandr; Karpenko, Sergii
The paper is targeted at the analysis of the importance of Automatic Dependent Surveillance-Broadcast (ADS-B) data in the terms of overcoming gaps between aircraft noise and local air quality modelling results and their short or long-term measurements. Presented results based on noise and air pollution measurement campaign at Ukrainian airports describe general peculiarities of the pre-processing and usage of ADS-B data during specific stages of aircraft landing and taking-off (LTO) cycle in the airport. The outcomes could be used for more accurate noise and air pollution exposure assessment and the development of recommendations for noise and local air quality monitoring systems in airports under consideration.